MODELLING OF STRESS-STRAIN STATE OF CRUSTAL SYSTEMS IN CONTEXT OF SPACE PROBLEM DURING THE GRANITE FORMATION - Лавренюк, М. (Київський національний університет імені Тараса Шевченка, 2013)
The problem of granites holds a special place in geology. Research of the granite formation problem leads to a number of partial problems, among those the question of depth of the granite generation and mechanisms of provision of space for large granitoid solids are distinguished. In the problem of space the geomechanical constituent is of primary importance. The major factors forming the stress-strain state in the system of the granite formation are permanently acting mass gravitation forces, tectonic forces of inter-slabs interaction, pseudo-mass forces, forces of volumetric thermoelastic effects, phase transitions in processes of metamorphism, metasomatism, partial and complete fusion. In existing investigations of stress-strain state of crust systems the geological mediums are supposed to be quasi-homogeneous. The objective of this work is to develop the general approach to computer modeling of the behavior of geological and mechanical systems of mega-blocks range, in context of space problem during the granite formation, taking into account structure anisotropy of the system. While the possibilities of full-size modeling of complex multifactorial magmatogene systems are limited, the possibilities of mathematical modeling are more appropriate, especially in view of the mechanical systems modeling. Verification of geological hypotheses and empirical data by constructing simple models with its further complication by means of transition to more and more complex combinations of force factors, rheological states, boundary conditions, and other factors is the most optimal. In the article the problem of stress-strain assessment of geological and mechanical system of mega-blocks range is analyzed. Assuming that the temperature of medium is known, there were obtained governing relations describing the behavior of geological and mechanical system at combined action of the gravity, non-homogeneous temperature field and power and kinematic influences imposed on the boundaries of considered system. The algorithm for solving of elastic problem is developed by means of the modified boundary element method. The governing relations of the considered problem are obtained as well as the numerical and analytical algorithm of stressstrain assessment of the considered geological and mechanical system is developed. Mathematical model and corresponding algorithm of the numerical calculation of stress-strain state of the considered system allow analyzing the stress-strain state of geological and mechanical system at combined action of gravity, non-homogeneous temperature field and imposed on the boundaries of considered system power and kinematic influences, taking into account structure anisotropy of the system. Thus the method proposed herein allows investigating the nature of stresses fields, and hence to forecast geometry of potential zones of relative decompression and tension, which are the most auspicious for granite formation.

В геології особливе місце займає проблема гранітів. Розгляд задачі гранітоутворення призводить до ряду часткових задач, серед яких вирізняються питання глибинності гранітоутворення та механізмів забезпечення простору для крупних гранітоподібних тіл. В проблемі простору геомеханічна складова має першочергову важливість. Головні чинники, що формують напружено-деформований стан в системі гранітоутворення –постійно діючі масові гравітаційні сили, тектонічні сили міжплитної взаємодії, псевдомасові сили об'ємних термопружних ефектів, фазових перетворень в процесах метаморфізму, метасоматозу, часткового і повного плавлення. В існуючих дослідженнях напружено-деформованого стану корових систем геологічні середовища вважаються квазіоднорідними. Метою роботи є побудова загального підходу до комп'ютерного моделювання поведінки геолого-механічних систем рангу мегаблоків в контексті проблеми простору під час гранітоутворення, з врахуванням структурної анізотропії системи. Оскільки можливості натурного моделювання складних багатофакторних магматогенних систем є обмеженими, більш доцільним є математичне моделювання, особливо в сенсі моделювання механічних систем. Найбільш оптимальним є перевірка геологічних гіпотез і емпіричних даних шляхом створення простих моделей з подальшим їх ускладненням за рахунок переходу до все більш складних комбінацій силових факторів, реологічних станів, граничних умов і т.д. В статті розглядається задача визначення напруженодеформованого стану геолого-механічної системи рангу мегаблоків. Вважаючи температуру середовища відомою, одержано визначальні співвідношення для описання поведінки геолого-механічної системи при сумісній дії на неї гравітації, неоднорідного температурного поля і заданих на границях системи силових і кінематичних впливів. Для побудови алгоритму розв'язання пружної задачі використовується модифікований метод граничних елементів. Одержано визначальні співвідношення розглядуваної задачі, побудовано чисельно-аналітичний алгоритм визначення напруженодеформованого стану розглядуваної геолого-механічної системи. Математична модель та відповідний алгоритм чисельного розрахунку напружено-деформованого стану розглядуваної системи дозволяють аналізувати напружено-деформований стан геолого-механічної системи при сумісній дії на неї гравітації, неоднорідного температурного поля і заданих на границях системи силових і кінематичних впливів, з врахуванням структурної анізотропію системи. Таким чином, запропонований метод дозволяє досліджувати характер полів напружень, а отже, прогнозувати геометрію потенційних областей відносної декомпресії та розтягу, які є найбільш сприятливі для гранітоутворення. Ключові слова: гранітоутворення, структурна анізотропія, термопружність.
МОДЕЛЮВАННЯ НАПРУЖЕНО-ДЕФОРМОВАНОГО СТАНУ КОРОВИХ СИСТЕМ В КОНТЕКСТІ ПРОБЛЕМИ ПРОСТОРУ ПІД ЧАС ГРАНІТОУТВОРЕННЯ